A construção sígnica no cinema de Hitchcock - Santos, Marcelo Moreira (2008)
This present work focuses on Movies as a hybrid form of representation, as the result of the union of three indissoluble, mixed, though distinct languages: the sound, the visual and the verbal ones. It seeks to understand the gearing of those languages in the signic construction of cinematographic works, notably in the case of Hitchcock. It is also the opportunity to highlight the profound signic revolution determined by the advent of images in movement in the end of the XIX century and by seeing, in the hybridism of the cinematographic discourse, a culmination of the esthetics of the fragmentary eighteenth century, notably the Baudelairean one, as it is armed by the fluctuating attention of the poet flâneur, in his dream of Modernity. We took as our main theoretical reference the Semiotics of Charles Sanders Peirce (1839-1914), who supplies the grounds for one to reflect on the epistemology of Movies, thus making possible the development of the analysis of the signic construction of Movies which, in the end, would constitute our understanding of the hybrid language of which they are made up of. Markedly limited by mixtures and juxtapositions of fragments, the cinematographic sign has its genesis delineated by the poetics of movement, by a poetics of inter-relations and exchanges between languages, which dialogs with the metropolitan environment in the end of the XIX century. With the objective of understanding this esthetics and such logic, found both in Movies and the Metropolis, one has sought the reflections of German philosopher Walter Benjamin on the flâneur and the phenomenological experience of the fragment, and the poetry of Charles Baudelaire, the flânerie and his modern dream of fluency amid the multitude, in his giving himself to fast-flowing, cut, abrupt phenomena of the chock. In the first chapter, we shall discuss to what extent the development of Movies is tied to the modern environment of the metropolis. On this path of reflection on the signic genesis of the Movies, it is a must that one investigates and questions the phenomenological nature of its hybrid language. In the second chapter, we shall observe the construction of the hybrid cinematographic sign and clarifies the triad that grounds it: its syntax, its form and its discourse. The third chapter analysis the film Vertigo by Alfred Hitchcock, and shows how, through the weaving of the visual, sound and verbal languages, this director creates, with a masterly hand, the thriller. In the Conclusion, besides reviewing all we have seen, the paper points at new ways one can understand the language of Movies, thus opening new inroads of questionings and hypotheses and deepening the theme and elaborating the horizons for the continuation of the research